Actividad antifúngica in vitro del aceite esencial de las hojas de Myrcianthes oreophila “Unkia” frente a Candida albicans - Benites Torres, Evelin Mirian (2018)
At present hundreds of plants are used in medicine, but modern science wants to know the active principles responsible for seeking their synthesis or propose structural changes in search of greater activity. The objective of this work was to determine the antifungal activity of the essential oil of the leaves of Myrcianthes oreophila "Unkia" against Candida albicans. To do this, 10 kg of leaves of Myrcianthes oreophila "Unkia" taxonomic identification No. 58317 were used, collected from the district of Llaugueda, province of Otuzco, La Libertad region. The extraction of the essential oil was carried out by the steam distillation method and to evaluate the antifungal activity, strain of Candida albicans ATCC 10231 was used, from the Microbiology Laboratory of the Faculty of Biological Sciences of the University Nacional de Trujillo, applying the Kirby-Bauer Method (agar diffusion). For the antifungal effect, experimental group I (25% essential oil) showed an average of 5.914 mm in diameter, for experimental group II (50% essential oil) it revealed an average of 13.498 mm in diameter and for the experimental group III (75% essential oil) of higher concentration presented an average of 28.476 mm in diameter. From this it is concluded that the essential oil of leaves of Myrcianthes oreophila "Unkia" has antifungal activity in vitro against Candida albicans